Analysis of the effect 3D printing parameters on tensile strength using Copper-PLA filament - Darsin, Mahros; Mauludy, Renald Rochman; Hardiatama, Intan; Fachri, Boy Arief; Ramadhan, Mochamad Edoward; Parningotan, Doddy (SINERGI, 2022)
This research aims to find the optimal combination of parameters to obtain the maximum tensile strength of 3D printing products made of eCopper, which consists of 45% Cu and 55% PLA. The parameters used were nozzle temperature, layer height, print speed and bed temperature with three levels each. The Taguchi L9 (3^4) experiment was used for design and analysis. The product was printed in the form of a tensile test specimen according to the ASTM D638 Type I standard using a Cartesian FDM 3D printer. The average response S/N ratio calculation found that the highest tensile strength would be obtained when applying combination parameters of nozzle temperature 230 oC, layer height 0.35 mm, print speed 90 mm/s and bed temperature 60 oC. While each parameter contributes to the tensile strength by the order are nozzle temperature, layer height, print speed, and bed temperature 59.44%, 20.53%, 18.06% and 1.97%, respectively.